Faktor-Faktor yang Berpengaruh Terhadap Tax Avoidance pada Perusahaan Manufaktur Tahun 2019 - 2021 - Ni Luh Putu Sandrya Dewi; Ni Luh Gde Novitasari; Muhammad Devin Ardiansyah (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Over the past five years, the percentage of tax revenue has fluctuated, starting in 2017 by 89.40%, increasing in 2018 to 92.41% and then decreasing to 84.44% in 2019 and in the last two years it has increased to 89.25% and 100, 18%, so it can be said that the realization of tax revenue has not been maximized. Paying taxes is a burden, so many companies choose to manipulate their taxes by carrying out tax avoidance. Tax avoidance is a practice of legal tax avoidance by exploiting loopholes in tax regulations. This study aims to examine the effect of the proportion of independent commissioners, audit committees, institutional ownership, sales growth and liquidity on tax avoidance in manufacturing companies from 2019 to 2021. The population in this study totaled 193 manufacturing companies listed on the Indonesia Stock Exchange (IDX). ) years 2019 – 2021. The sample in this study was 73 companies which were determined based on a purposive sampling technique. The analysis technique used in this study uses multiple linear analysis. The results showed that the proportion of independent commissioners and audit committees had a negative effect on tax avoidance while institutional ownership, sales growth and liquidity had no effect on tax avoidance. Future research is expected to use other variables because in this study there are 3 variables that have no effect.